PENANAMAN JENIS ENDEMIK LOKAL DALAM UPAYA REHABILITASI HUTAN DI KAWASAN TAHURA SULTAN THAHA SYAIFUDDIN, JAMBI - Hendra Kurniawan; Citra Rahmatia; Riko Kurniawan; Sri Muryati; Amelia Retno Eka Putri; Faradilla Herlin (Jurnal SOLMA, 2026)
Forest damage due to human activities has become an environmental problem that has resulted in a decline in ecosystem quality and biodiversity. This activity aims to increase community awareness and participation in forest rehabilitation through the planting of local endemic species in the Sultan Thaha Syaifuddin Grand Forest Park (Tahura STS), Jambi. The method used is a participatory approach through counseling, training, and direct practice of tree planting which is carried out in stages starting from socialization to monitoring and evaluation. The results of the activity show that community participation and understanding have increased, and the planting of Mahogany (Swietenia mahagoni) and Sengon (Paraserianthes falcataria) species showed a good level of initial adaptation to local environmental conditions. Ecologically, this activity contributed to increasing vegetation cover and improving environmental quality, while socio-economically it increased community capacity and opened up opportunities for sustainable use of forest resources. In conclusion, a local species-based rehabilitation approach with active community involvement has proven effective in supporting sustainable forest conservation efforts.